PENGARUH REWARD DAN PUNISHMENT TERHADAP KEDISIPLINAN GURU DI TK AL WAHYU SURABAYA - Dian Anggraini (MOTORIC, 2021)
The teacher must have a disciplined attitute, as a role model for his students. However, in TK Al Wahyu. From 18 teachers, some of them are undisciplined, especially in terms of attendance to school. The writer tries to provide a solution to the above problems in the form of the application of reward and punishment in the hope of being able to improve teacher discipline. The writer conduct the study for 2 months as much as 2 cycles of the type of school action research. From the results of the first cycle, there were 3 people (16,7%) who were absen once, 4 people (22,2%)who were absen twice and 5 people (27,8%) who were absen more than 3 times. Then in the second cycle, the result shown improvement. There were 2 people (11,1%) who were absen once, 1 people (5,6%) who were absen twice and 0 people who were absen exceed 3 times. Therefore, it concludes that reward and punishment is effective to increase teacher discipline in TK Al Wahyu.